Narasi Queer dalam Gim “Coming Out Simulator 2014” - Kusuma, Ida Bagus Eka Dharma; Joni, I Dewa Ayu Sugiarica; Gelgel, Ni Made Ras Amanda; Damasemil, Calvin (E-Jurnal Medium, 2023)
Views on sex are shaped by social and political forces and are linked in important ways to those around class, race, and particularly gender. This view resides in speech acts in everyday life as well as present as discourse, which is continued, treated, and challenged through communication, one of which is through the medium of video games. In this study, the researcher uses van Dijk's critical discourse analysis model to understand the discourse of sexuality in the game